2012
DOI: 10.1002/chem.201101940
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Self‐Assembly of a Bioinspired Alkyl Catechol at a Solid/Liquid Interface: Competitive Interfacial, Noncovalent, and Solvent Interactions

Abstract: The large tendency of catechol rings to adsorb on surfaces has been studied by STM experiments with molecular resolution combined with molecular-dynamics simulations. The strong adhesion is due to interactions with the surface and solvent effects. Moreover, the thermodynamic control over the differential adsorption of 1 and the nonanoic solvent molecules has been used to induce a new temperature-induced switchable interconversion. Two different phases that differ in their crystal packing and the presence of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 58 publications
0
34
1
Order By: Relevance
“…Host-guest experiments showed that these two networks can selectively adsorb fullerene molecules, such as C 60 , C 70 , and C 80 , as guests. [77]. This transformation should contribute to the isomerization of the azobenzene unit in NN4A.…”
Section: Light-driven Reversible Phase Transformationmentioning
confidence: 94%
See 2 more Smart Citations
“…Host-guest experiments showed that these two networks can selectively adsorb fullerene molecules, such as C 60 , C 70 , and C 80 , as guests. [77]. This transformation should contribute to the isomerization of the azobenzene unit in NN4A.…”
Section: Light-driven Reversible Phase Transformationmentioning
confidence: 94%
“…[72] Catechols and their derivatives are found in nature, taking part in a remarkably broad scope of biochemical processes and functions that range from the adhesive properties of marine organisms to the storage of some transition metal ions. [77] At room temperature (20 8C), the catechols form a molecular array with domains (i.e., the a phase) that extend from 10 nm up to a few hundred nanometers. [73][74][75][76] In a recent study, Saiz-Poseu and colleagues demonstrated that temperature control could be used to switch between two different lamellae of the alkylated catechols at the nonanoic acid/HOPG interface.…”
Section: Temperature-driven Reversible Phase Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, self‐assembled monolayers (SAM) with enhanced adhesion properties that mimic mussels have been reported for the use of 4‐(6′‐mercaptohexyl)catechol on different gold surfaces . Relevant information on the basic principles that govern the adhesion of catechols at the solid–liquid interface has also been obtained upon studying the self‐assembly of these molecules on different surfaces with STM . The precise development and immobilization of functionalized self‐assembled structures has also provided new (bio)active coatings with promising clinical or technological applications .…”
Section: Introductionmentioning
confidence: 99%
“…[8] Relevant information on the basic principles that govern the adhesion of catechols at the solid-liquid interface has also been obtainedu pon studying the self-assembly of thesem olecules on different surfaces with STM. [9] The precise development and immobilization of functionalized self-assembled structures has also provided new (bio)activec oatings with promising clinical or technological applications. [10] Moreover,s upramolecular selfassemblyd riven by catechol/metal ion coordination has afforded the fabrication of novel functional materials, including adhesives,capsules, coatings, andhydrogels, [11] and the formation of coordination polymer nanoparticles of technological relevance in different areas, such as molecular electronicso rn anomedicine.…”
Section: Introductionmentioning
confidence: 99%